Statistical Consulting and Collaboration Techniques - Mbachu, Hope Ifeyinwa; Nwanya, Julius; Dozie, Kelechi; Raymond, Mirian (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
Statistical consulting and collaboration techniques create an opportunity for statistical consulting and collaboration for researchers through individual meetings and support for interdisciplinary research projects. Part of the activities of statistical consulting and collaboration is to study the design and analysis plans, perform data analysis, interpret results and prepare grants and publications. Considered on one end of the spectrum are long-term consultations, which are occasionally called collaboration in academic settings. On the other end are short-term consultations. A statistical consultant is a problem solver and is communication in every field of study and problems associated with it. Therefore, the skills required for effective capacity building in statistical consulting and collaboration among Laboratory for Interdisciplinary Statistical Analysis (LISA) stat labs across developing countries in Africa are discussed. A statistical consulting model is considered. This chapter considers the advantages and benefits of implementing proper statistical consulting and collaboration techniques. Activities of a LISA stat lab practised within and outside higher institutions in developing countries are provided. Also provided is the need for improvement and benefit of capacity building of stat labs in statistical consulting and collaboration techniques.